2019
DOI: 10.1108/md-11-2018-1180
|View full text |Cite
|
Sign up to set email alerts
|

Does leader humility matter? Effects on altruism and innovation

Abstract: Purpose The purpose of this paper is to analyze the effect of leader humility in firm innovativeness. The study highlights the importance of promoting altruism within organizations as a mechanism that may explain why leader humility fosters innovation. Design/methodology/approach The study was conducted in a sample frame of 11,594 Spanish companies. In total, 568 valid questionnaires were obtained and 284 different companies participated in the study. Structural equations were used to validate the proposed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 59 publications
3
54
0
5
Order By: Relevance
“…Humble leaders can psychologically empower followers by inducing many features of self-concepts (Owens et al , 2013). For example, humble leadership acknowledges the contribution of the subordinates to the organizational goals (Mallén et al , 2019; Naseer et al , 2019), treats the followers with compassion, respect and admiration (Argandona, 2015) that give the feelings to the subordinates that their work is meaningful for them and have an impact over organizational outcomes (Chen et al , 2018). Humble leaders also give value to their followers' contributions and suggestions that enhance followers' confidence (Jeung and Yoon, 2018) and self-efficacy about their jobs (Bandura, 1986; Conger and Kanungo, 1988) and enhance their level of competence.…”
Section: The Mediating Role Of Psychological Empowermentmentioning
confidence: 99%
See 1 more Smart Citation
“…Humble leaders can psychologically empower followers by inducing many features of self-concepts (Owens et al , 2013). For example, humble leadership acknowledges the contribution of the subordinates to the organizational goals (Mallén et al , 2019; Naseer et al , 2019), treats the followers with compassion, respect and admiration (Argandona, 2015) that give the feelings to the subordinates that their work is meaningful for them and have an impact over organizational outcomes (Chen et al , 2018). Humble leaders also give value to their followers' contributions and suggestions that enhance followers' confidence (Jeung and Yoon, 2018) and self-efficacy about their jobs (Bandura, 1986; Conger and Kanungo, 1988) and enhance their level of competence.…”
Section: The Mediating Role Of Psychological Empowermentmentioning
confidence: 99%
“…Innovation occurs when an employee develops, promotes and implements new ideas as critical components of IWB (Janssen, 2000). Humble leadership role reflects the appreciation of subordinates' expertise (Mallén et al , 2019) that develops self-confidence among the subordinates to practice their creative thinking (Zhang and Zhou, 2014). IWB can lead the employees to quickly resolve work-related problems (Zhou and Wu, 2018), which is an essential determinant of organizational success (Scott and Bruce, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…According to Murat Ar and Baki 79 , idea-generating includes promoting new ideas, marketing good ideas, developing solutions, and inspiring workers to discover innovative conduct to solve problems. Mallén, et al 9 also indicated that humble leadership's impact on creativity would be more substantial where specific organisational environments facilitate idea generation existing and involved rather than inactive or absent. Risktaking and idea implementation are closely associated with innovation 80 .…”
Section: Discussionmentioning
confidence: 99%
“…Humble leadership promotes followers to put on fresh ideas and generate an environment where innovative approaches are encouraged to inspire workers to establish inventive solutions before a suitable method is selected 6 . Furthermore, the humble leader makes their subordinates resilient toward precariousness by teachability and responsiveness to criticism and encourages their team members to attempt new things based on trial and error (Mallén et al, 2019) that stimulate creativity among them the followers 35 .…”
Section: The Mediating Role Of Employee Creativitymentioning
confidence: 99%
See 1 more Smart Citation